2022
DOI: 10.1093/eurheartj/ehac145
|View full text |Cite
|
Sign up to set email alerts
|

Importance of genetic testing in unexplained cardiac arrest

Abstract: Aims Genetic testing is recommended in specific inherited heart diseases but its role remains unclear and it is not currently recommended in unexplained cardiac arrest (UCA). We sought to assess the yield and clinical utility of genetic testing in UCA using whole-exome sequencing (WES). Methods and results Survivors of UCA requiring external defibrillation were included from the Cardiac Arrest Survivor with Preserved Ejection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…liver or spleen) should be retained for potential genetic analysis. Other sources of DNA such as blood spots and tissue stored in suitable media at room temperature may suffice. 15 , 413–416 When a SCD could be attributable to a likely genetic cause, post‐mortem genetic testing in the deceased individual targeted to the likely cause should be performed. 414 , expert opinionWhen a SCD remains unexplained despite an autopsy and toxicology, post‐mortem genetic testing in the deceased individual targeted to channelopathy genes should be performed when the circumstances and/or family history support a primary electrical disease. 15 , 415 , 416 When a SCD <50 years old remains unexplained despite an autopsy, toxicology and channelopathy gene panel testing, post‐mortem genetic testing in the deceased individual may be extended to a wider panel including cardiomyopathy genes. 15 , 415 , 416 In a decedent with unexplained SCD or an UCA survivor, hypothesis‐free (post‐mortem) genetic testing using exome or genome sequencing should not be performed. Expert opinionIn selected UCA survivors with idiopathic VF, genetic testing for founder variants, a where relevant, should be considered. 417 In UCA survivors, genetic testing of channelopathy and cardiomyopathy genes may be considered. 418–421 In relatives of UCA survivors or SCD decedents in whom a pathogenic variant has been identified, predictive genetic testing should be performed. 413 , 422 In relatives of UCA survivors or SCD decedents, clinical evaluation of 1st degree family members should be performed, and targeted to the index case’s phenotype if present. 422–427 In decedents with SCD or survivors with cardiac arrest in whom a non‐genetic cause has been identified, genetic testing of the index case and clinical evaluation of relatives should not be performed. Expert opinion…”
Section: State Of Genetic Testing For Sudden Cardiac Death or Survivo...mentioning
confidence: 99%
See 2 more Smart Citations
“…liver or spleen) should be retained for potential genetic analysis. Other sources of DNA such as blood spots and tissue stored in suitable media at room temperature may suffice. 15 , 413–416 When a SCD could be attributable to a likely genetic cause, post‐mortem genetic testing in the deceased individual targeted to the likely cause should be performed. 414 , expert opinionWhen a SCD remains unexplained despite an autopsy and toxicology, post‐mortem genetic testing in the deceased individual targeted to channelopathy genes should be performed when the circumstances and/or family history support a primary electrical disease. 15 , 415 , 416 When a SCD <50 years old remains unexplained despite an autopsy, toxicology and channelopathy gene panel testing, post‐mortem genetic testing in the deceased individual may be extended to a wider panel including cardiomyopathy genes. 15 , 415 , 416 In a decedent with unexplained SCD or an UCA survivor, hypothesis‐free (post‐mortem) genetic testing using exome or genome sequencing should not be performed. Expert opinionIn selected UCA survivors with idiopathic VF, genetic testing for founder variants, a where relevant, should be considered. 417 In UCA survivors, genetic testing of channelopathy and cardiomyopathy genes may be considered. 418–421 In relatives of UCA survivors or SCD decedents in whom a pathogenic variant has been identified, predictive genetic testing should be performed. 413 , 422 In relatives of UCA survivors or SCD decedents, clinical evaluation of 1st degree family members should be performed, and targeted to the index case’s phenotype if present. 422–427 In decedents with SCD or survivors with cardiac arrest in whom a non‐genetic cause has been identified, genetic testing of the index case and clinical evaluation of relatives should not be performed. Expert opinion…”
Section: State Of Genetic Testing For Sudden Cardiac Death or Survivo...mentioning
confidence: 99%
“…Recently, WES with virtual panel analysis performed systematically in 228 survivors of cardiac arrest of uncertain aetiology was shown to identify a pathogenic variant in 10% of cases. 421…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(34) Studies found pathogenic and likely pathogenic variants in CMP genes in patients with unexplained cardiac arrest, highlighting the arrhythmogenic potential of such variants in the absence of apparent CMP features. (35,36) Other effect modifiers in the clinical setting include exercise and inflammation, which might promote development of phenotype or CMP-related complications. (30) However, the increased mortality may not necessarily be due to higher rates of sudden cardiac death—it is all-cause in this study, and this warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, WES with virtual panel analysis performed systematically in 228 survivors of cardiac arrest of uncertain aetiology was shown to identify a pathogenic variant in 10% of cases. 421 Trio WES on amniocentesis or CVS samples may be performed in prenatal cases with syndromic and/or complex CHD.…”
Section: Introductionmentioning
confidence: 99%